VD_FINDINFO HC / 2018 / 120 vom 18. Dezember 2017 - VD Tribunal cantonal (2017)
CONTRAT D'ENTREPRISE, FORFAIT, ENRICHISSEMENT ILLÉGITIME, STIPULATION POUR AUTRUI, COURTAGE, PLUS-VALUE | 112 CO, 363 CO, 373 CO, 62 al. 2 CO